2021
DOI: 10.1016/j.it.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Dual Nature of Type I Interferons in SARS-CoV-2-Induced Inflammation

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The ability of our cells to secrete type-I interferons (IFN-I) is essential for the control of virus replication and for effective anti-viral immune responses; for this reason, viruses have evolved the means to antagonize IFN-I. Inhibition of IFN-I production is pronounced in SARS-CoV-2 infection, which can impair the adaptive immune response and exacerbate inflammatory disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 107 publications
3
105
0
3
Order By: Relevance
“…Moreover, interfering with type I IFN signaling can redirect immunity to enable control of viral infection ( 41 ). In fact, the dual nature of type I IFNs in SARS-CoV-2induced inflammation has recently been elegantly reviewed by others ( 42 ). The observation that these drugs also reduced syncytia formation are intriguing since they suggest that complement may also influences the biology of the virus in cells CD46, the receptor for C3b, the other major product of C3 processing, is known to enhance syncytia formation in other viral infections ( 43 ), so it is possible that reducing active C3 also reduces syncytia formation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interfering with type I IFN signaling can redirect immunity to enable control of viral infection ( 41 ). In fact, the dual nature of type I IFNs in SARS-CoV-2induced inflammation has recently been elegantly reviewed by others ( 42 ). The observation that these drugs also reduced syncytia formation are intriguing since they suggest that complement may also influences the biology of the virus in cells CD46, the receptor for C3b, the other major product of C3 processing, is known to enhance syncytia formation in other viral infections ( 43 ), so it is possible that reducing active C3 also reduces syncytia formation.…”
Section: Discussionmentioning
confidence: 99%
“…They found that IFN-I treatment is associated with positive clinical outcomes regarding mortality and discharge (56). The time to start IFN-I treatment might be crucial (57).…”
Section: Introductionmentioning
confidence: 99%
“…Disagreements related to the role of IFN-I in patients with COVID-19 demonstrate the importance of further studying these cytokines in the disease. The importance of IFN-I in the pathogenesis of the COVID-19 had been previously reviewed (30,(57)(58)(59)(60)(61). Nonetheless, the available evidence regarding the circulating levels of IFN-I and its response and the association with the severity of the disease has not been meta-analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…elsewhere (3,4). In brief, IFN-I comprises a mixture of IFNβ, multiple subtypes of IFN-α, and several other IFNs.…”
mentioning
confidence: 99%